Development of the Android-Based Educational Game Media “Perjalanan Si Maya” as a Formative Assessment to Improve Critical Thinking Skills and Interest in Learning Science for Elementary School Students - Devi Falamila Putri Anggraeni; Wahono Widodo; Zainul Arifin Imam Supardi (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research aims to develop an android-based educational game media, "Perjalanan Si Maya," as a formative assessment to improve critical thinking skills and interest in learning elementary school students. Method: This research is a type of development research (R&D). The development method used in this research is ADDIE (Analyse, Design, Development, Implementation, and Evaluation). Results: The results showed that the development of an android-based educational game media, "Perjalanan Si Maya," as a formative assessment was declared valid based on acquiring the very valid category. The result of practicality is classified as very good (very practical). The result of effectiveness Based on N-Gain, the mean value of the control class obtained a mean value in the "less effective" category. In contrast, the experimental class obtained a mean value in the "moderately effective" category. The results of student learning interest have increased from before learning to after learning using educational game media “Perjalanan Si Maya. Novelty: Teachers can carry out formative assessments through educational games to train students' critical thinking skills and interest in learning to become more qualified, effective, and efficient.